Country readiness and prerequisites for successful design and transition to implementation of essential packages of health services: experience from six countries. (19th January 2023) - Alwan, Ala; Majdzadeh, Reza; Yamey, Gavin; Blanchet, Karl; Hailu, Alemayehu; Jama, Mohamed; Johansson, Kjell Arne; Musa, Mohammed Yusuf Ahmed; Mwalim, Omar; Norheim, Ole Frithjof; Safi, Najibullah; Siddiqi, Sameen; et al.
Abstract : This paper reviews the experience of six low-income and lower middle-income countries in setting their own essential packages of health services (EPHS), with the purpose of identifying the key requirements for the successful design and transition to implementation of the packages in the context of accelerating progress towards universal health coverage (UHC). The analysis is based on input from three meetings of a knowledge network established by the Disease Control Priorities 3 Country Translation Project and working groups, supplemented by a survey of participating countries. All countries endorsed the Sustainable Development Goals target 3.8 on UHC for achievement by 2030. The assessment of country experiences found that health system strengthening and mobilising and sustaining health financing are major challenges. EPHS implementation is more likely when health system gaps are addressed and when there are realistic and sustainable financing prospects. However, health system assessments were inadequate and the government planning and finance sectors were not consistently engaged in setting the EPHS in most of the countries studied. There was also a need for greater engagement with community and civil society representatives, academia and the private sector in package design. Leadership and reinforcement of technical and managerial capacity are critical in the transition from EPHS design to sustained implementation, as are strong human resources and country ownership of the process. Political commitment beyond the health sector is key, particularly commitment from parliamentarians and policymakers in the planning and finance sectors. National ownership, institutionalisation of technical and managerial capacity and reinforcing human resources are critical for success. The review concludes that four prerequisites are crucial for a successful EPHS: (1) sustained high-level commitment, (2) sustainable financing, (3) health system readiness, and (4) institutionalisation.